Evaluation of an educational intervention on arbovirus prevention at basic school no. 1973 "Costa Alegre" in the city of Coronel Oviedo, year 2024. - Ríos Mujica, Patricia; Segovia Barboza, Catalina Elizabeth; Estigarribia Sanabria, Gladys Mercedes; Méndez, Julieta; Viveros de Cabello, Guiomar; González, Gloria; Galeano, Deisy (Medicina Clínica y Social, 2025)
Introduction: Arbovirosis represent a major global public health concern due to their high prevalence and concentration in tropical and subtropical regions. They are mainly transmitted by Aedes aegypti and may cause clinical manifestations ranging from mild to severe. Objective: To evaluate the impact of an educational intervention on arbovirosis prevention at Costa Alegre School in Coronel Oviedo during 2024. Materials and Methodology: A longitudinal quasi-experimental study was conducted among fourth, fifth, and sixth-grade students between July and September 2024. A validated questionnaire developed by Vivas was applied, consisting of 10 knowledge questions (scored 0–1) and 6 skills questions assessed with a Likert scale. The Pan American Health Organization’s arbovirosis prevention booklet was used as educational material. Data were analyzed with Stata 16. Results: In the pretest, 27% of students demonstrated insufficient knowledge and 73% sufficient knowledge; in the post-test, sufficient knowledge increased to 99% and insufficient knowledge decreased to 1%. The McNemar test revealed a statistically significant increase in correct responses after the intervention (p < 0.001). Regarding skills, the Wilcoxon test indicated a moderate but significant improvement (p < 0.05), reflecting positive changes in preventive practices such as household cleaning, use of repellents, and control of water containers. Conclusion: The educational intervention significantly improved students’ knowledge and prevention skills, confirming its effectiveness as a school-based health promotion strategy. Replication in other educational and community settings is recommended to evaluate its long-term impact and applicability. Future studies should explore complementary strategies to strengthen learning and promote sustainable preventive practices